Class system using the IPA to improve phonemes (/n/, /ŋ/) in english - Vicente Giron, Nathaly Silvana; Cedillo Suconota, Mayely Angeline (Machala: Universidad Técnica de Machala, 2025)
This research aims to improve the pronunciation of the English phonemes /n/ and /ŋ/ in students of 7th grade, class “A”, at NA school General Basic Education during the 2025–2026 academic year, through the implementation of a class system based on the use of the International Phonetic Alphabet (IPA). The study is framed within the existing problems in the Ecuadorian education system, where the teaching of English tends to focus on grammatical aspects, neglecting phonetic and oral development, which has a direct impact on the intelligibility and communicative competence of students. The study recognizes pronunciation as a crucial skill in learning English as a foreign language and identifies persistent challenges in the Ecuadorian educational context, including traditional teaching approaches, limited phonetic instruction, and a lack of dynamic didactic resources. Applying a quantitative, non-experimental, crosssectional, and descriptive methodology, diagnostic evaluations, interviews, and classroom observations were conducted to assess students’ pronunciation level. The results revealed considerable difficulties in articulating and recognizing the target phonemes. In response, a phonetics-based class system using the IPA was developed and implemented to strengthen both articulatory and auditory awareness, and to improve oral communication skills.The findings demonstrate that incorporating the IPA as a didactic resorce is effective in enhancing students’ pronunciation. This proposal serves as a replicable educational model to improve English pronunciation through innovative and structured teaching strategies.
La presente investigación tiene como objetivo mejorar la pronunciación de los fonemas /n/, /ŋ/ del inglés en los estudiantes de 7mo grado de Educación General Básica paralelo “A” de la unidad educativa NN, durante el periodo lectivo 2025-2026, mediante la implementación de un sistema de clases basado en el uso del Alfabeto Fonético Internacional (IPA). El estudio se enmarca en la problemática existente dentro del sistema educativo ecuatoriano, donde la enseñanza del inglés suele centrarse en aspectos gramaticales, descuidando el desarrollo fonético y oral, lo cual repercute directamente en la inteligibilidad y competencia comunicativa de los estudiantes. La tesis parte del reconocimiento de que la pronunciación es una habilidad esencial en el aprendizaje del inglés como lengua extranjera, y que existen limitaciones significativas en el contexto educativo ecuatoriano, tales como la enseñanza tradicional, la escasa instrucción fonética y la falta de recursos didácticos. A través de un enfoque metodológico cuantitativo y un diseño de tipo transversal-descriptivo, se aplicaron instrumentos como pruebas diagnósticas, entrevistas y observación para identificar las dificultades de pronunciación en los estudiantes. Los resultados evidencian un bajo desarrollo de la competencia fonética, especialmente en la articulación y reconocimiento auditivo de los fonemas /n/, /ŋ/. A partir de este diagnóstico, se diseñó e implemento un sistema de clases que integra teoría y práctica fonética con el apoyo del IPA, orientando a fortalecer la conciencia articulatoria y auditiva, y promover una pronunciación más precisa y comunicativa. La propuesta demuestra que el uso del IPA como recurso didáctico innovador es efectivo para mejorar la pronunciación en inglés, y se plantea como una herramienta viable para ser aplicada en otros contextos educativos similares, contribuyendo así a la mejora del proceso de enseñanza-aprendizaje del idioma.
Keywords: PRONUNCIACION; FONEMAS /N/ Y /Ŋ/; ALFABETO FONETICO INTERNACIONAL (IPA); SISTEMA DE CLASES; EDUCACION GENERAL BASICA.